Construction of fluorescent transgenic zebrafish Tg(amh:mCherry) and tracer analysis of its gonadal development - WU Jing; XU Yue; LING Shiying; SONG Huaidong; QIAO Jie; DONG Mei (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To establish a transgenic zebrafish line Tg(amh:mCherry) for studying gonadal development and related diseases, and to trace and analyze the developmental process of zebrafish gonads.Methods·A recombinant transgenic expression vector pTol2-amh-mCherry was constructed by using the upstream promoter sequence of the zebrafish anti-Müllerian hormone (amh) gene coding region and the gene coding sequence of the red fluorescent protein, and was validated by using Sanger sequencing. The recombinant transgenic expression vector and mRNA of Tol2 transposase were co-microinjected into zebrafish embryos, and fluorescent zebrafish were selected by using fluorescence microscope to screen for a stable inherited transgenic zebrafish line Tg(amh:mCherry). In situ hybridization was used to detect whether the location of the fluorescence signals was consistent with the location of endogenous expression of amh. The red fluorescence of transgenic zebrafish from generation F3 was observed by fluorescence microscopy, and the process of gonadal development was tracked and analyzed.Results·The recombinant transgenic expression vector pTol2-amh-mCherry was successfully constructed, and a stable inherited F3 generation transgenic zebrafish line Tg(amh:mCherry) was successfully established. The results of in situ hybridization showed that the location of the red fluorescence signals in the transgenic zebrafish Tg(amh:mCherry) was consistent with the location of endogenous expression of amh. Through observation and analysis of the fluorescence of transgenic zebrafish from F3 generation, five developmental patterns of zebrafish gonads were found.Conclusion·The successful construction of Tg(amh: mCherry) transgenic zebrafish line facilitates the tracer analysis of zebrafish gonadal development, which provides a better experimental model for the study of gonad-related diseases.